Stunting Knowledge and Attitudes among Adolescents in Banjar Pande, Sayan Village, Ubud, Gianyar: The Effect of Structured Education - Komalasari, Ni Luh Putu Ratih; Oktaviani, Ni Putu Wiwik; Trisnadewi, Ni Wayan; Adiputra, I Made Sudarma; Wahyudi, Hendro (Basic and Applied Nursing Research Journal, 2024)
Introduction: Stunting is a chronic nutritional problem that remains a major threat to the quality of human resources. One of the efforts to break the stunting cycle is through the active role of youth. However, many adolescents are still unaware of stunting, so it is necessary to increase adolescent knowledge by providing structured education. The aim of this study was to determine the effect of structured education on adolescents' knowledge and attitudes about stunting. Methods: This study is pre-experimental research with a pretest-posttest one-group design. The sample size was 34 people, selected using a purposive sampling technique. Structured education was provided through modules and video media three times, conducted once a week for 45 minutes. Results: The results of the study showed that the average pretest score for adolescents' knowledge was 11.97, and the posttest score was 16.26. The average pretest score for adolescents' attitudes was 37.68, and the posttest score was 55.21. The results of the Wilcoxon signed-ranks test for knowledge showed a p-value of 0.000 < 0.05, and for attitudes, it also showed a p-value of 0.000 < 0.05, indicating that there was an effect of structured education on adolescents' knowledge and attitudes about stunting. Conclusion: Structured education using modules and video media is an effective method to convey messages in an understandable and engaging way, enabling the target audience to learn the material well, increasing adolescents' knowledge about stunting and encouraging the formation of positive attitudes.